2014
DOI: 10.1155/2014/189268
|View full text |Cite
|
Sign up to set email alerts
|

Response Time, Visual Search Strategy, and Anticipatory Skills in Volleyball Players

Abstract: This paper aimed at comparing expert and novice volleyball players in a visuomotor task using realistic stimuli. Videos of a volleyball setter performing offensive action were presented to participants, while their eye movements were recorded by a head-mounted video based eye tracker. Participants were asked to foresee the direction (forward or backward) of the setter's toss by pressing one of two keys. Key-press response time, response accuracy, and gaze behaviour were measured from the first frame showing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
54
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 31 publications
6
54
0
9
Order By: Relevance
“…The specificity of football requires a state of readiness to respond to stimuli that may arise in the field of view. When it comes to volleyball players, our results are in line with the observations of Piras et al (2014) and Vansteenkiste et al (2014) who evaluated the reaction time based on the video of registered sequences of volleyball actions. Also, studies of other authors (Kokubu et al 2006;Kioumourtzoglou et al 1998;Zwierko et al 2010) confirmed shorter reaction times straight in volleyball players compared to non-athletes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The specificity of football requires a state of readiness to respond to stimuli that may arise in the field of view. When it comes to volleyball players, our results are in line with the observations of Piras et al (2014) and Vansteenkiste et al (2014) who evaluated the reaction time based on the video of registered sequences of volleyball actions. Also, studies of other authors (Kokubu et al 2006;Kioumourtzoglou et al 1998;Zwierko et al 2010) confirmed shorter reaction times straight in volleyball players compared to non-athletes.…”
Section: Discussionsupporting
confidence: 89%
“…For example, Baylor and Spirduso (1988) found that regular physical activity improves the efficiency of simple reaction times, more with regards to the pre-motor fraction (70%) than to motor fraction of the reaction time (30%). Many researchers confirm this thesis, reporting faster response times in athletes in comparison with non-athletes (Ando, Kida, Oda, 2001;Kioumourtzoglou, Kourtessis, Michalopoulou, Derri, 1998;Kokubu, Ando, Kida, Oda, 2006;Overney, Blanke, Herzog, 2008;Piras, Lobietti, Squatrito, 2014;Vansteenkiste, Vaeyens, Zeuwts, Philippaerts, Lenoir, 2014;Zwierko, Osiński, Lubiński, Czepita, Florkiewicz, 2010). On the other hand, not all articles confirm the existence of a relationship between the efficiency of motor reactions and physical fitness (Cojocarlu and Abalasel …”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, it was demonstrated that the experts have greater fixation on relevant tasks and less in non relevant tasks, accompanied by short fixation time and allocation of selective attention 14 . Similar results were observed in the study of Piras, Lobietti and Squatrito 22 where expert volleyball players were compared to novice players in a visuomotor task using video scenes of real games in attack situations. The experts with greater performance on the task were associated with lower number of visual fixations and the visual fixations were performed faster.…”
Section: Discussionsupporting
confidence: 83%
“…Assim, a atenção, as estratégias de busca visual, a antecipação, a seleção e execução da resposta, são cruciais para um bom desempenho nos esportes coletivos 2,3 . Em uma perspectiva cognitivista, a cognição permite a interpretação de acontecimentos, atribuindo significado aos mesmos.…”
Section: Introductionunclassified